On Justification in Moral Education - Prendergast, Emma (Philosophical Inquiry in Education, 2025)
Teachers engaged in moral education face a puzzle. We aim to bring children up to believe in and subscribe to basic moral standards such as prohibitions against harming others and requirements to help when we can. At the same time, there is widespread reasonable disagreement about the content and justification of morality, and teaching standards as justified when there is reasonable disagreement is wrongfully indoctrinatory. I analyze two answers to the puzzle, posed by Hand (2018a) and White (2016), defending White’s education in altruism approach against Hand’s criticisms by drawing from an analogy with the teaching of standards and principles in other subjects. Moral standards need not be metaethically justified to children all the way down, like how we need not teach children the metaphysical foundations of math and science in order to teach the standards of math and science in a way that does not wrongfully indoctrinate them. I conclude in favor of a pluralistic approach to teaching the reasons to abide by basic moral standards.